Evaluación de la diversidad y abundancia de grupos funcionales de macro y meso invertebrados en cinco sistemas de producción en Cotopaxi, 2024. - Cuchiparte Toapanta, Jorge Samuel (2024)
The health of the soil is given by the presence of macro and meso invertebrates. Healthy soils have high edaphic biodiversity, contributing to the balance of the ecosystem. This research aimed to evaluate the diversity and abundance of functional groups of macro and meso invertebrates in five production systems: traditional, agroecological, conventional, degraded and natural. To capture invertebrates, three sampling methods were used, such as soil monoliths, pitfall traps and “Berlese-Tullgren” funnels. They were assessed by different schemes, to later be identified through taxonomic keys and with the use of the iNaturalist application. To obtain the results, statistical analysis and the Shannon-Wiener diversity index for equity and Simpson for dominance were used. A total of 667 individuals referring to macro invertebrates and 129 meso invertebrates were recorded; The most diverse order being the Coleoptera (199), followed by Araneae (138), Diptera (122), Hymenoptera (65), Isópoda (63) and Haplotaxida (63). For the UTC-Campus Salache zone, in the traditional system the dominant functional group was the predators (62.5%) referring to the order Araneae. For the community of Isinche de Infantes the functional group detritivores, herbivores and predators dominates in the natural system (66.66%) and in the community of Carrillos it was the same functional group (63.63%), which belongs to the order Coleoptera. The highest Shannon-Wiener diversity and abundance indices in the three sampling areas was 1.69 for the natural system in UTC-Salache; 1.96 in the traditional system of Isinche de Infantes and 1.57 in the agroecological system in the Community of Carrillos; These values represent moderate diversity. Simpson's index determined dominance in Isinche in the natural system with 0.50; This shows that there is a dominance of one or two species; in the same way in UTC-Salache. But, for Carrillos in the degraded system it was lower (0.40) with a similarity of dominance. At the conclusion of this study, it can be shown that in the traditional scheme the largest number of individuals was witnessed by the three areas; This may be due to the fact that the traditional systems of the province have a low use of agricultural inputs and high biodiversity of plants that make up their habitat. This research also highlights the importance of arthropods capturing methods of using easy-to-apply techniques and thereby determining soil health.